Design and circular economy. Architectures that regenerate the built fabric - Gerardo Semprebon; Kevin Santus; Stefano Sartorio; Arianna Luisa Nicoletta Scaioli (Agathón)
Although the circular economy has occupied a crucial place in the development agendas of industrialized countries in recent years, the construction sector still seems far from a mature understanding of the cultural dimensions related to the notion of circularity since, until now, its focus has been mainly on improving technological solutions. However, the circular economy opens up new operational frontiers beyond the scale of the construction detail. It embraces more complex social and cultural fields that ultimately question the changing relationship between man and inhabited space. The article assumes this perspective and examines the possible implications of circular logics’ spatial organizations at larger scales that have a great impact on settlement forms, proposing a critical comparison between two case studies characterized by two built fabrics with different densities. The first one is the regeneration of the Ilot de l’Arc de Triomphe district (high density and compactness), and the second one is the transformation of Contrada Bricconi (low density and rarefaction). The two design experiences ensurie a second life to inhabited artifacts and soils.